MENINGKATKAN PERILAKU SOSIAL ANAK USIA 5-6 TAHUN MELALUI METODE BERMAIN PERAN DI PAUD PELANGI KASIH KECAMATAN TENAYAN RAYA KOTA PEKANBARU Julimawar - Julimawar Simanjuntak; Tri Utami; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : The purpose of this study are as follows: 1) To determine Is the role play method can improve the social behavior of children aged 5-6 years old in early childhood Pelangi Kasih District of Tenayan Raya Pekanbaru. 2) To find out How can I improve the social behavior of children aged 5-6 years in early childhood Pelangi Kasih District of Tenayan Raya Pekanbaru 3) To know the improvements are the social behavior of children aged 5-6 years after the method of playing a role in early childhood Pelangi Kasih District of Tenayan Raya Pekanbaru. The subjects were PAUD Pelangi Kasih District of Tenayan Raya Pekanbaru, amounting to as many children as 15 children, consisting of five men and 10 women. Collecting data using observation, documentation and interview. Based on the survey results revealed that an increase in Social Behavior obtained prior to action for the first cycle increased by 30.7%. While the increase in the Social Behavior of the first cycle to cycle II of 80.8%, and the overall increase in the Social Behavior of the preliminary data for the second cycle of 97.0%. Conclusion The hypothesis testing is proposed in this research that says "There is an increased Social Behaviour Children Aged 5-6 Years Through Role Playing Method in ECD Pelangi Kasih District of Tenayan Raya Pekanbaru," unacceptable".Keywords : Social behavior, role playing method